SISTEM INFORMASI GEOGRAFIS PEMETAAN TITIK RAWAN KECELAKAAN DAERAH SUMATERA BARAT BERBASIS WEB - Saputra, Heru; Stephane, Ilfa; Karfindo, Karfindo; Jelita, Silis (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2018)
Geographic Information System (GIS) is a system designed to work with spatially-referenced data or geographic coordinates. According to data owned by Traffic Directorate of West Sumatra Police, the number of accident-prone areas in West Sumatra is 48 points. This leads to the need for a Geographic Information System of accident-prone areas in West Sumatra based on the web to describe the map of vulnerable area locations along with the information needed. Geographic Information System Application of Web-Based Accident Complex, with programming languages (JavaScript and PHP), MySQL as database and Google Maps API. The result of this research is the creation of a web-based GIS application that can present information about the location of accident-prone areas in West Sumatra in detail and can be accessed easily be used people.